Qualidade de aplicação de inseticida na cultura do milho por um veículo aéreo não tripulado - Tartari, Gustavo (2024)
The present work investigates the quality of insecticide application in corn crops using an Unmanned Aerial Vehicle (UAV), popularly known as a drone. The study was conducted in the context of the growing importance of corn in the Brazilian economy and the need for effective methods of applying agricultural pesticides. The main objectives of the research were to evaluate the effectiveness of spraying carried out by drones, identify the factors that affect the deposition of the pesticide on plants in the application technique using UAVs. Parameters such as volumetric mean diameter (DMV), droplet density, spray deposition, relative amplitude (Span) and percentage of coverage were analyzed. The work was developed through field experiments, at different application rates (7.5 15 and 22.5 L ha−1) and two types of spray tips (XR 11001 and TXA 8001) were tested. Data collection involved the use of water-sensitive papers to measure the distribution of the insecticide and the assessment of weather conditions that could interfere with application. The results indicated that drones offer a viable and efficient alternative for applying insecticides to corn crops, presenting advantages in terms of precision and reduction of environmental impacts. However, the research also highlighted the importance and need for constant monitoring of weather conditions to ensure maximum effectiveness. The conclusion of this work points to the significant potential of drones in modernizing agriculture, recommending the adoption of this technology by producers, as long as it is accompanied by appropriate management and equipment regulation practices.